What they understand is not necessarily important to practice: Exploring halal literacy learning in high school students - Iis Aisyah; Dian Friantoro; Muhammad Dzulfaqori Jatnika (Inovasi Kurikulum, 2024)
Halal literacy has not become an important thing for high school students. Even though high school students or teenagers, in the future, will be the main consumers of halal products in Indonesia. The purpose of this study is to determine the Halal Literacy Index in high school students using the level of approval and the level of importance to be practiced. This study uses a quantitative descriptive approach. The respondents studied were 334 high school students in Tasikmalaya, West Java. The results showed that high school students have a higher level of approval than the level of importance to practice. It was found that of all the items, the student's level of approval has an average of 4.327 so it falls into the "Agree" criteria towards the halal concept. While the level of importance to be practiced has an average of 3.047 so it falls into the "Neutral" criteria for the importance of practicing the concept of halal in everyday life. This shows that what is approved is not necessarily important to be practiced for high school students.   Abstrak Literasi halal belum menjadi hal yang penting bagi kalangan Siswa Sekolah Menengah Atas. Padahal Siswa SMA atau remaja, di masa depan akan menjadi konsumen utama produk halal di Indonesia. Tujuan dari penelitian ini adalah untuk menentukan Indeks Literasi Halal pada siswa sekolah menengah atas menggunakan tingkat persetujuan dan tingkat kepentingan untuk dipraktekkan. Penelitian ini menggunakan pendekatan deskriptif kuantitatif. Responden yang diteliti sebanyak 334 siswa SMA di Tasikmalaya, Jawa Barat. Hasil penelitian menunjukkan bahwa siswa sekolah menengah atas memiliki tingkat persetujuan yang lebih tinggi daripada tingkat kepentingan untuk mempraktikkan. Ditemukan bahwa dari semua item, tingkat persetujuan siswa memiliki rata-rata 4.327 sehingga masuk dalam kriteria "Setuju" terhadap konsep halal. Sedangkan tingkat kepentingan untuk dipraktikkan memiliki rata-rata 3.047 sehingga masuk dalam kriteria "Netral" terhadap kepentingan untuk mempraktekkan konsep halal dalam kehidupan sehari-hari. Ini menunjukkan bahwa apa yang disetujui belum tentu penting untuk dipraktikkan bagi kalangan siswa sekolah menengah atas. Kata Kunci: literasi halal; sekolah menengah atas; pembelajaran literasi halal; peserta didik